Asian Development Bank and Asian Infrastructure Investment Bank – is cooperation possible? - Smolaga, Mateusz (Overcoming Controversies in East Asia, 2017)
The Asian Development Bank (ADB) is a well-known financial institution operating in the Asia-Pacific region since 1966. The rise of this multilateral organization was sponsored mainly by Japan, for which, no doubt, it is still an important instrument of external policy. However, nowadays the ADB constitutes 67 members (48 regional and 19 non-regional), including PR China. With an impressive budget (ca. 20 billion) and focus areas ranging from social development to information technologies, the ADB is an important source of development funding. The Asian Infrastructure Investment Bank (AIIB) is a rather new initiative, only opening up for business in January 2016. Based in Beijing, it is a multilateral organization comprising 57 founding members (37 regional members and 20 nonregional partners), excluding Japan and the United States. The creation of the AIIB is a reaction to the fiasco of the transformation of global financial institutions like the International Monetary Fund and the World Bank Group. China’s intentions in initiating the AIIB are clearly something other than altruism. It might be seen as part of a win-win economic cooperation strategy that could benefit both regional and national development processes. Like the ADB, the AIIB focuses on the development of infrastructure and other productive sectors in the Asia-Pacific region. The question is, should we anticipate strong rivalry between these two institutions, as political realism would suggest, or will the ADB and the AIIB find a way to offer their best to the Asia- Pacific countries without any major conflict?